Palliative effect of taurine against hepatic injury induced by polystyrene microplastics through antioxidant and metabolic pathway modulation in mice - A. Eskandrani, Areej; Abdel-Rahman Mohamed, Amany; Alotaibi, Badriyah S.; Abd El-Hakim, Yasmina M.; Khamis, Tarek; E. Noreldin, Ahmed; E Abdelhamid, Ahmed; Alsubaie, Nawal; Alqahtani, Leena S. (Frontiers in Pharmacology, 2025)
IntroductionMicroplastics (MPs), particularly polystyrene microplastics (PS-MPs), are emerging environmental contaminants that have been shown to accumulate in various organs, including the liver, leading to oxidative stress, inflammation, and metabolic dysregulation. However, the precise molecular mechanisms underlying PS-MP-induced hepatotoxicity and disruptions in lipid metabolism remain poorly understood. Taurine (Tau), a naturally occurring amino acid with known antioxidant and cytoprotective properties, may suggest a potential protective strategy against such toxicity. This study aimed to investigate the hepatotoxic effects of PS-MPs in a mouse model and to evaluate the potential ameliorative role of Tau.MethodsMice were exposed to PS-MPs with or without Tau supplementation over a 60-day experimental period. The groups were: control group, which received distilled water orally (0.5 mL/mouse). The Tau group was administered Tau at a dose of 200 mg/kg body weight. The PS-MPs group received PS-MPs at 10 mg/kg body weight, suspended in distilled water. The combination group (PS-MPs + Tau) received both Tau and PS-MPs at the same doses concurrently. Multiple endpoints were assessed, including oxidative stress biomarkers, liver function indicators, lipid and bilirubin profiles, histopathological alterations, and the expression of key genes involved in lipid metabolism and oxidative stress regulation.ResultsExposure to PS-MPs resulted in notable hepatic injury, characterized by elevated oxidative stress, dysregulated lipid profiles, impaired antioxidant enzyme activity, and altered expression of genes related to lipogenesis and fatty acid oxidation compared to the control. Histological examination revealed congested central and portal veins, massive aggregations of lymphocytes, the hepatocytes appeared markedly swollen, disorganized arrangement, and exhibited large nuclei with strong basophilic staining consistent with these biochemical findings. Co-administration of Tau mitigated these adverse effects, improving antioxidant status, normalizing metabolic markers, and partially restoring gene expression patterns and tissue integrity.ConclusionOverall, the findings indicated that PS-MPs caused liver damage via oxidative stress and lipid metabolic disturbance, and that Tau supplementation had a protective effect, possibly via modulating oxidative and metabolic pathways. This experiment emphasized the necessity for additional research into Tau as a therapeutic agent in microplastic-related liver damage.